Fun Pattern Based Learning Approach for Social Studies Learning during the Covid-19 Pandemic - Tetep Tetep; Alni Dahlena (STAI Hubbulwathan Duri, 2021)
In the current situation, students consider a less exciting subject and less motivated to learn social studies. So that students tend to be less enthusiastic when participating in learning, especially in distance learning. This study aims to describe social studies learning innovations for students based on fun educational games for students. This research method is a qualitative method using case study techniques directly on students and literature students. The results of this study are; (1) social studies learning strategies based on fun educational games related to simple social studies materials, but packaged in interesting patterns for students so that they can increase students motivation and interest in learning, especially in social studies learning; (2) Increasing the optimization of students in understanding social studies materials with the concept of strengthening reflection in social studies learning, especially in the introduction of regions and cultures in Indonesia.